Economic assessment of use of pond ash in pavements - Sarkar, Raju; Dawson, Andrew (2015)
The paper introduces a new type of industrial waste-based subbase material which can replace conventional subbase material (CSM) in pavement construction. Utilisation of this industrial waste, namely pond coal ash produced from a thermal power plant in road construction will help to reduce the disposal problem of this waste and also will help to reduce the problem of scarcity of CSM. Lime and fibre were also added to the pond ash at various percentages to improve the suitability of this type of mix as subbase material. The optimum service life of pavement is studied with the help of numerical modelling and the cost benefit is also presented in the current study. The study reveals that stabilisation of the coal ash with 2% lime may produce an optimal material and, even though a greater thickness may be required to deliver the same pavement performance, direct cost savings of around 10% may be achieved in addition to less easily quantifiable environmental benefits. Design charts are provided to exploit the findings.